2021
DOI: 10.1016/j.psj.2021.101164
|View full text |Cite
|
Sign up to set email alerts
|

Chicken embryo as a model in epigenetic research

Abstract: Epigenetics is defined as the study of changes in gene function that are mitotically or meiotically heritable and do not lead to a change in DNA sequence. Epigenetic modifications are important mechanisms that fine tune the expression of genes in response to extracellular signals and environmental changes. In vertebrates, crucial epigenetic reprogramming events occur during early embryogenesis and germ cell development. Chicken embryo, which develops external to the mother's body, can be easily manipulated in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 120 publications
(135 reference statements)
0
28
0
5
Order By: Relevance
“…The IOT has the potential to use chicken embryos as a powerful model for epigenetic research. The use of chicken embryos for epigenetic studies surpasses the benefits of mammalian models because the chicken embryo develops fast, the blastoderm is easily accessible, and the embryo grows external to the body ( 7 ).…”
Section: Applications Of In Ovo Technologymentioning
confidence: 99%
See 1 more Smart Citation
“…The IOT has the potential to use chicken embryos as a powerful model for epigenetic research. The use of chicken embryos for epigenetic studies surpasses the benefits of mammalian models because the chicken embryo develops fast, the blastoderm is easily accessible, and the embryo grows external to the body ( 7 ).…”
Section: Applications Of In Ovo Technologymentioning
confidence: 99%
“…Subsequently, the success of in ovo vaccination (IOV) has set forth a paradigm shift in the poultry industry by adapting IOT to harness more benefits by changing the embryonic milieu and improving the nutritional conditions of neonatal chicks. Besides IOV, this technology is being utilized with ramifications to deliver growth promoting compounds and nutrients at the embryonic stage ( in ovo feeding, IOF) ( 4 ), to improve the performance and gut health of poultry ( 5 ), to determine the sex of the embryo ( in ovo sexing) ( 6 ), and to initiate epigenetic changes that improve the health and production status of the poultry at post-hatch period ( 7 ). The term IOF, in ovo stimulation, in ovo injection (IOI), in ovo delivery (IOD), and in ovo supplementation (IOS) are often interchangeably used as they are not well-differentiated.…”
Section: Introductionmentioning
confidence: 99%
“…To better understand the potential of epigenetic mechanisms after bioactive substances administered in ovo, it is necessary to analyze the direct effects and their intergenerational and/or transgenerational inheritance ( Bednarczyk et al, 2021 ). The epigenetic effects can be classified into two categories: the so-called “context-dependent” or “germline-dependent” ( Burggren, 2015 ).…”
Section: Transgenerational Effectsmentioning
confidence: 99%
“…Numerous studies ( Bentz et al, 2016 ; Li et al, 2016 ; Vinoth et al, 2018 ) have demonstrated inter- or multi-generational effects of changing environment in birds and also different developmental epigenetic patterns have been studied in various chicken types ( Bednarczyk et al, 2021 ). These studies have proved that the chicken transcriptome could be reprogrammed by manipulation of different environmental factors during early embryogenesis.…”
Section: Transgenerational Effectsmentioning
confidence: 99%
“…Subsequently, using chick embryos has profoundly influenced developmental biology since the middle of the 20th century [ 3 , 24 ], not only for understanding the fundamental processes in development, but also in the function of modeling human development and disorders, as previously summarized in some landmark papers and comprehensive reviews [ 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ].…”
Section: Introductionmentioning
confidence: 99%